The entrepreneurial character of the library profession - Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2008)
We believe that librarians have a proactive attitude to give better services to their users, and to have a specific role in the present social context characterized by an enormous cultural and informative offer. To justify this opinion we describe good practices and experiences of the Spanish public libraries.
Keywords: Good practices; Public libraries; Librarians; Entrepreneurship.